REVITALISASI JUDICIAL PARDON DALAM PEMBARUAN HUKUM ACARA PIDANA DI INDONESIA - Sutrisno, Umar Wiyogo; Irawan, Andrie; Pradana, Aditya Fajri Kurnia (AL HUKMU: Journal of Islamic Law and Economics, 2024)
This study aims to determine and analyse the relevance of revitalising judicial pardon in the field of criminal procedure law reform in Indonesia. In general, judicial pardon, or the original legal term judicial clemency, is one of the legal instruments that considers judges in giving punishment to convicts who are legally found guilty according to criminal procedure law in consideration of justice and humanity. In Indonesia, legal management in the field of judicial pardon is still less than optimal. This research is conducted in a normative juridical manner with a qualitative approach, by analysing primary and secondary legal materials and in-depth literature. Thus, the results of this research can conclude that the revitalisation of judicial pardon can make a positive contribution to a fairer and more humanist criminal justice system. This revitalisation includes strengthening the legal foundation, increasing the capacity of judges, and establishing a more transparent and accountable oversight mechanism. As a result of better implementation, judicial pardons can reduce injustice in the criminal justice system, overcrowding of correctional institutions, and support the rehabilitation and reintegration of prisoners. Therefore, the reform of Indonesia's criminal procedure law could include judicial pardons as one of the necessary aspects to achieve closer protection of sub/iller justice.